2014
DOI: 10.1007/s10803-014-2203-x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Correlates of Service Access Among Youth with Autism Transitioning to Adulthood

Abstract: This study examined service receipt and unmet service needs among youth with autism spectrum disorders (ASD) in their last year of high school, as well as the youth (intellectual disability, race/ethnicity, autism severity, comorbid psychiatric diagnoses, behavior problems, adaptive behavior) and family (income, parental health, parental depressive symptoms, parental anxiety) correlates of service access. Thirty-nine families of youth with ASD participated. Data were collected via parental interview/questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 49 publications
4
97
0
1
Order By: Relevance
“…This suggests effects of internalizing problems on social and other adaptive behavior deficits beyond those associated with ASD alone, which may shed light on findings of particularly high service need in individuals with ASD and comorbid psychiatric disorder. 43 It also points to the need for thoughtful development of targeted treatments for internalizing problems in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests effects of internalizing problems on social and other adaptive behavior deficits beyond those associated with ASD alone, which may shed light on findings of particularly high service need in individuals with ASD and comorbid psychiatric disorder. 43 It also points to the need for thoughtful development of targeted treatments for internalizing problems in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Groups were assigned using a random number generator, stratified by project site and whether the youth had ID in addition to ASD. Because an ID diagnosis is a significant determinant of disability service access among youth with ASD (Taylor & Henninger, 2015), we stratified by this variable to ensure that any group differences in services could not be attributed to unequal distributions of youth who had ID. Similarly, we wanted to ensure that any group differences could not be attributed to different proportions in each group of those who were taking the program in-person (at the host site) vs. through distance technology.…”
Section: Methodsmentioning
confidence: 99%
“…23 The authors of the remaining 2 studies directly recruited families of adults with autism. 34,35 Sample sizes ranged from 39 to 17 818 people. The age of participants with autism ranged from 12 to 26 years, and the mean proportion of sample members who were male was 85%.…”
Section: Sample Characteristics and Methodological Attributesmentioning
confidence: 99%
“…50 Parents of TAY with autism have also reported that many services were not provided in a geographic area or were not convenient or accessible. 35 Other factors (like the number of job openings and community views of disability) may also contribute to the experiences and outcomes of TAY. Including descriptive variables, such as those drawn from census tracts or through geocoding, or TAY's subjective appraisals of neighborhood quality may help to identify which neighborhood factors are important to transition success.…”
Section: Community Levelmentioning
confidence: 99%